Safety and activity of alisertib, an investigational aurora kinase A inhibitor, in patients with breast cancer, small-cell lung cancer, non-small-cell lung cancer, head and neck squamous-cell carcinoma, and gastro-oesophageal adenocarcinoma: a five-arm phase 2 study - Melichar, Bohuslav; Adenis, Antoine; Lockhart, A Craig; Bennouna, Jaafar; Dees, E Claire; Kayaleh, Omar; Obermannova, Radka; DeMichele, Angela; Zatloukal, Petr; Zhang, Bin; Ullmann, Claudio Dansky; Schusterbauer, Claudia (The Lancet. Oncology, 2015)
BACKGROUND: Alisertib is an investigational, oral, selective inhibitor of aurora kinase A. We aimed to investigate the safety and activity of single-agent alisertib in patients with predefined types of advanced solid tumours. METHODS: We did a multicentre phase 1/2 study at 40 centres in four countries (Czech Republic, France, Poland, and the USA). Here, we report results from phase 2; enrolment for the study began on Feb 16, 2010, and ended on May 3, 2013. Adult patients were eligible for the study if they had either breast cancer, small-cell lung cancer, non-small-cell lung cancer, head and neck squamous-cell carcinoma, or gastro-oesophageal adenocarcinoma that had relapsed or was refractory to chemotherapy. Patients had to have undergone two or fewer previous cytotoxic regimens (four or fewer for breast cancer patients), not including adjuvant or neoadjuvant treatments. Enrolment followed a two-stage design: to proceed to the second stage, two or more objective responses were needed in the first 20 response-assessable patients in each of the five tumour cohorts. Alisertib was administered orally in 21-day cycles at the recommended phase 2 dose of 50 mg twice daily for 7 days followed by a break of 14 days. The protocol-specified primary endpoint was the proportion of patients with an objective response, assessed by Response Evaluation Criteria In Solid Tumors version 1.1 in the response-assessable population (ie, patients with measurable disease who received at least one dose of alisertib and had undergone at least one post-baseline tumour assessment). This completed trial is registered with ClinicalTrials.gov, NCT01045421. FINDINGS: By May 31, 2013, 249 patients had been treated, 53 with breast cancer, 60 with small-cell lung cancer, 26 with non-small-cell lung cancer, 55 with head and neck squamous-cell carcinoma, and 55 with gastro-oesophageal adenocarcinoma. Among response-assessable patients, an objective response was noted in nine (18%, 95% CI 9-32) of 49 women with breast cancer, ten (21%, 10-35) of 48 participants with small-cell lung cancer, one (4%, 0-22) of 23 patients with non-small-cell lung cancer, four (9%, 2-21) of 45 people with head and neck squamous-cell carcinoma, and four (9%, 2-20) of 47 individuals with gastro-oesophageal adenocarcinoma; all were partial responses. Adverse events were similar across tumour types. The most frequent drug-related grade 3-4 adverse events included neutropenia (n=107 [43%]), leukopenia (53 [21%]), and anaemia (26 [10%]). Serious drug-related adverse events were reported in 108 (43%) patients. INTERPRETATION: These data support further clinical assessment of alisertib in patients with solid tumours, particularly those with breast cancer and small-cell lung cancer. FUNDING: Millennium Pharmaceuticals, Inc, a wholly owned subsidiary of Takeda Pharmaceutical Company Limited.
Keywords: Small Cell Lung Carcinoma; Disease-Free Survival; Male; France; Carcinoma, Non-Small-Cell Lung; Esophageal Neoplasms; Pyrimidines; nádory hlavy a krku; Aged; Head and Neck Neoplasms; nádory prsu; senioři; Francie; mužské pohlaví; malobuněčný karcinom plic; nežádoucí účinky léčiv; nádory jícnu; Aurora kinasa A; lidé; Aurora Kinase A; ženské pohlaví; adenokarcinom; Breast Neoplasms; nemalobuněčný karcinom plic; pyrimidiny; Azepines; Humans; Adenocarcinoma; Drug-Related Side Effects and Adverse Reactions; azepiny; Female; lidé středního věku; přežití bez známek nemoci; Middle Aged